Screening tools for autism in culturally and linguistically diverse paediatric populations: a systematic review - Elmee Huda; Patrick Hawker; Sara Cibralic; James Rufus John; Aniqa Hussain; Antonio Mendoza Diaz; Valsamma Eapen (BMC, 2024)
Abstract Background Autism Spectrum Disorder (ASD) has varying prevalence rates worldwide, often higher in culturally diverse populations. Cultural differences can affect autism symptom recognition. Language barriers and differing healthcare attitudes may delay diagnosis and intervention. Most autism screening tools were developed in Western, predominantly Caucasian populations, and their appropriateness in culturally and linguistically diverse (CALD) contexts remains uncertain. There is a lack of comprehensive data on the accuracy of these tools in identifying autism in culturally and linguistically diverse groups. Consequently, it is unclear whether current screening tools are culturally sensitive and appropriate. Methods A research protocol was registered in PROSPERO (CRD42022367308). A comprehensive search of literature published from inception to October 2022 was conducted using the following databases: PubMed, Medline Complete, Scopus, PsychInfo and CINAHL Complete. The articles were screened using pre-determined inclusion and exclusion criteria. Data extracted included participant demographics, screening tool psychometric properties (validity, reliability, accuracy) and acceptability. A narrative synthesis approach was used. Results From the initial retrieval of 2310 citations, 51 articles were included for analysis. The studies were conducted in 32 different countries with screening tools in the following languages: Chinese, Spanish, Korean, Turkish, Arabic, Kurdish, Persian, Serbian, Italian, French, Sinhala, Taiwanese, Finnish, Northern Soho, Albanian, German, Japanese, Vietnamese, Farsi, Greek and English. There was no data on acceptability of the screening tools in CALD populations. Validity, reliability, and accuracy ranged from poor to excellent with consistently high performance by screening tools devised within the populations they are intended for. Conclusions The review evaluated autism screening tools in culturally diverse populations, with a focus on validity, reliability, and acceptability. It highlighted variations in the effectiveness of these tools across different cultures, with high performance by tools devised specifically for the intended population, emphasizing the need for culturally sensitive screening tools. Further research is needed to improve culturally specific, reliable autism screening tools for equitable assessment and intervention in diverse communities.